Do Women Managers Lower Gender Pay Gaps? Evidence from Public and Private Firms. Issue 4 (2nd October 2019) - Magda, Iga; Cukrowska-Torzewska, Ewa
ABSTRACT: This paper analyzes the link between the share of women managers and the size of the firm-level gender pay gap, looking separately at the private and public sectors. Using a large linked employer–employee dataset for Poland and nonparametric and parametric decompositions, the study finds that a greater share of women managers is associated with an increased advantage for women in selected types of public-sector units: the ones in which remunerations of women and men are already equal, and a large share of the workforce is tertiary-educated. The effects are, however, relatively small in size. In private establishments, lower gender wage inequality is associated with higher shares of women workers, but not women managers.